Implementation fidelity of a voluntary sector-led diabetes education programme. Issue 1 (2nd January 2018) - Kok, Michele S.Y.; Jones, Mat; Solomon-Moore, Emma; Smith, Jane R.
Abstract : Purpose: The quality of voluntary sector-led community health programmes is an important concern for service users, providers and commissioners. Research on the fidelity of programme implementation offers a basis for assessing and further enhancing practice. The purpose of this paper is to report on the fidelity assessment of Living Well Taking Control (LWTC) – a voluntary sector-led, community-based education programme in England focussing on the prevention and management of type 2 diabetes. Design/methodology/approach: This fidelity of implementation (FoI) study was conducted with the Devon-based LWTC programme. A fidelity checklist was developed to analyse audio records of group-based lifestyle education sessions – implementation was rated in terms of adherence to protocol and competence in delivery; the influence of wider contextual factors was also assessed. Kappa statistics ( κ ) were used to test for inter-rater agreement. Course satisfaction data were used as a supplementary indicator of facilitator competence. Findings: Analysis of 28 sessions, from five diabetes prevention and two diabetes management groups (total participants, n =49), yielded an overall implementation fidelity score of 77.3 per cent for adherence (moderate inter-rater agreement, κ =0.60) and 95.1 per cent for competence (good inter-rater agreement, κ =0.71). The diabetes prevention groups consistently achieved higher adherence scores than the diabetes management groups. Facilitator competence was supported by high participant satisfaction ratings. Originality/value: An appropriate level of implementation fidelity was delivered for the LWTC group-based education programme, which provides some confidence that outcomes from the programme reflected intervention effectiveness. This study demonstrates the viability of assessing the FoI in a voluntary sector-led public health initiative and the potential of this method for assuring quality and informing service development.